Exploring Features and Products in E-Commerce on Consumers Behavior Using Cognitive Affective - Pahrudin Pahrudin; Rezzy Eko Caraka; Li-Wei Liu; Prana Ugiana Gio; Nur Anita Yunikawati; Bens Pardamean (IEEE Access)
Technology advancement has given rise to a new online purchasing paradigm known as e-commerce. Online shopping in e-commerce platform has altered consumer behavior and purchasing decisions. However, a few studies have conducted by considering cognitive-affective process in making purchase decision on e-commerce. Therefore, the current study examines consumer behavior from perspective of stimulus-organism-response theory and the internal perception process (cognitive and affective) to understand consumer’s purchase decisions. We use Structural Equation Model-Partial Least Square technique to analyze the data of 308 consumers in Indonesia. Our findings report that two dimensions of the stimulus environment (credibility and product usefulness) significantly contributed to perceived trust; convenience has an insignificant impact on perceived trust and perceived value. In comparison, three dimensions of the stimulus environment (convenience, informativeness, and product price) contribute to consumers’ perceived trust. Furthermore, the stimulus environment indicators (credibility, informativeness, product price, and product usefulness) effect on perceived value, while convenience has an insignificant on consumers’ perceived value. The internal perception process or cognitive and affective process, perceived trust has an insignificant impact on perceived pleasure, while perceived value has a significant impact on perceived pleasure. Lastly, perceived pleasure significantly influences consumer purchase decisions in online shopping and e-commerce. The findings of this study can expand the research on e-commerce how consumer’s consider their cognitive and affective factor on product purchase decision. The study suggests that the optimize the features and products as way to improve the consumer purchase decision, and it affects toward cognitive and affective components such as perceive trust, value, and pleasure. This study has contributed both theoretically and practically to stakeholders, policy makers, and practitioner in e-commerce.